Pentingnya Psikologi Pendidikan Agama Kristen dalam Proses Pembelajaran - Yemima Meidina Rista Br Sembiring; Eniawati Ndruru; Sriwati Sihombing; Martina Labora Nainggolan; Agriva J.Pandiangan; Yuki Tambunan; Wilson Simajuntak (Lembaga Pengembangan Kinerja Dosen, 2025)
Christian Religious Education (PAK) is a process of developing the whole person, emphasizing mastery of theological knowledge and fostering the character, emotions, and spirituality of students to become like Christ. In situations like this, educational psychology is crucial because it helps teachers comprehensively understand the dynamics of student behavior, motivation, and developmental stages. Christian Religious Education teachers can utilize an educational psychology approach to build a more contextual learning process and meet students' spiritual needs. An understanding of psychological theories such as Jean Piaget's cognitive development, Abraham Maslow's motivational theory, Albert Bandura's social learning theory, and Carl Rogers' humanistic approach provides a scientific foundation for Christian Religious Education teachers to implement teaching strategies appropriate to students' developmental stages and personalities. From a Christian perspective, the integration of psychology and theology allows for learning that is not only cognitive but also transformative, encouraging students to experience real growth in faith and a deeper relationship with God. The integration of psychological principles and Christian values ​​not only improves the quality of learning but also reaffirms the primary mission of Christian Religious Education: to develop individuals with faith and character who are able to live out God's love in their daily lives. Therefore, understanding and applying educational psychology is not merely an optional option, but a fundamental necessity in building a Christian Religious Education learning paradigm that is relevant, contextual, and meaningful for today's generation.